Hand hygiene: knowledge, attitude and practices among mothers of under 5 children attending a tertiary care hospital in North India - Gupta, Rajiv Kumar; Singh, Parveen; Rani, Renu; Kumari, Rashmi; Gupta, Chandini; Gupta, Riya (International Journal Of Community Medicine And Public Health, 2018)
Background: Hand hygiene remains the most cost effective strategy in prevention of health care associated infections as it may limit or completely stop the transmission of microorganisms. Poor hand hygiene practices, especially of the mothers of under five children are likely to pose a major threat to the health of their children. The present study aimed to assess the knowledge, attitude and practices of under-five mothers visiting an outpatient department in a tertiary teaching care hospital in North India. Methods: This cross-sectional study was conducted among 330 mothers who were attending with their under five children in paediatrics OPD of Government Medical College, Jammu. A self-administered questionnaire which was pilot tested was administered to the consenting mothers. The questionnaire consisted of socio demographic information followed by knowledge, attitudes and practices of the respondents about hand washing. Results: Knowledge about spread of disease was excellent among the respondents. Other knowledge parameters like responsibility of mother to ensure proper hand washing among children and long nails can spread bacteria were better among the urban mothers (p<0.05). Similarly attitudes of the urban mothers were found to be more favourable especially about towel sharing and teaching children about proper hand washing (p<0.05). Practices like usage of soap and water after defecation were found to be excellent among both the urban and rural respondents. However higher proportion of urban females reminded their children about hand washing before and after eating (p<0.05). Conclusions: The study results reveal a better knowledge, attitude and practices among urban mothers in comparison to their rural counterparts. This necessitates community awareness generation regarding hand hygiene, more so in rural mothers, so that many communicable diseases which could be transmitted by improper hand hygiene are taken care of.